PENERAPAN KEGIATAN MENGGUNTING DALAM MENINGKATKAN KEMAMPUAN MOTORIK HALUS KELOMPOK B - Syifa Safitiri; Saripah; Dewi Ferawati (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2022)
Child fine motor development is very importaint in developing child skills. fine motor skills at the age of 5-6 years as initial capital in stimulating children's writing skills needed for learning at the next education level. One of the activities that are effective in developing children's fine motor skills is through cutting activities. This research was conducted using a qualitative approach with descriptive research type. The data sources used were teachers, children and school principals. Data collection techniques by interview, observation and documentation. The results showed that the development of fine motor skills of children through cutting activities aims to practice moving the wrists, fingers, and creativity and imagination of children. The teacher's way to improve fine motor skills through cutting activities starts from attracting children's attention, preparing attractive equipment, introducing pictures to children and letting children be creative and have their own imagination. The implications of coloring activities in developing children's fine motor skills include being proficient in using colored pencils, being able to coordinate their eyes and hands, and developing children's self-help skills.